2022
DOI: 10.1681/asn.2021081142
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Interaction of HLA-DPB1 and Proteinase 3 in ANCA Vasculitis is Associated with Clinical Disease Activity

Abstract: Background: PR3-ANCA vasculitis has a genetic association with HLA-DPB1. We explored immunologic and clinical features related to the interaction of HLA-DPB1*04:01 with a strongly binding PR3 peptide epitope (PR3225-239). Methods: ANCA vasculitis patients with active disease and in remission were followed longitudinally. Peripheral blood mononuclear cells from patients and healthy controls with HLA-DPB1*04:01 were tested for HLA-DPB1*04:01 expression and interaction with a PR3 peptide identified via in silico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
2
17
1
Order By: Relevance
“…Additionally, our results underscore that disease phenotype in ANCA vasculitis may be contingent on autoantigen availability resulting from dysregulated autoantigen gene expression. We have previously shown that an epitope-specific response drives T cell response in MPO- and PR3-ANCA ( 14 , 15 ). Increased presence of pathogenic autoantigen epitopes may further impact the adaptive response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our results underscore that disease phenotype in ANCA vasculitis may be contingent on autoantigen availability resulting from dysregulated autoantigen gene expression. We have previously shown that an epitope-specific response drives T cell response in MPO- and PR3-ANCA ( 14 , 15 ). Increased presence of pathogenic autoantigen epitopes may further impact the adaptive response.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of relapse within the PR3-ANCA cohort was not based on variant carrier status. Possible explanations include other clinical differences in patients with PR3-ANCA or other genetic influences, such as HLA variants, that predispose patients with PR3-ANCA to likelihood of relapse ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Volume-regulated anion currents (VRACs) were first described in 1988, 2 and their electrophysiologic properties have been examined in a variety of cell types. 3,4 However, the molecular identity of VRACs remained enigmatic for a long time until the leucine-rich repeat-containing 8 member A channel (LRRC8A; also known as SWELL1) was identified in 2014. 5,6 LRRC8A can itself form functional hexamers, or it may assemble in herteromers with other members, including LRRC8B, LRRC8C, LRRC8D, and LRRC8E, to produce anion-conducting channels with unique biophysical properties.…”
mentioning
confidence: 99%
“…The re-emergence of measurable B cell autoimmunity, in the form of PR3-ANCA, increases the risk of relapse, but ANCA cannot be used alone to dictate therapy. Assessing both T and B cell autoimmunity with other markers of inflammation, may allow for better definition of immunologic remission and improved assessment of the risk and detection of relapse 3 . In this issue of JASN Chen et al 3 begin to address this issue by examining PR3-specific CD4+ T cells in PR3-AAV.…”
mentioning
confidence: 99%
See 1 more Smart Citation